Grey Model for Stream Flow Prediction - Vishnu B; Syamala P (Graduate Program of Syiah Kuala University, 2012)
Abstract – Design, operation and planning of water resources, irrigation and water supply systems require estimation of stream flow. A grey system or stochastic approach is required for dealing with the hydrological complexities of mid and long-term stream flow prediction. Generally relatively long period data series of stream flow records is required for the prediction using stochastic methods. In developing countries like India, availability of long period hydrological records is a problem. Grey system theory is applicable in the case of unclear inner relationship, uncertain mechanisms and insufficient information and requires only small samples for parameter estimation. Stream flow records of Bharathapuzha river basin, Kerala, India is subjected to grey analysis. Model parameters were estimated using leastsquares method. Statistical indices for the developed models indicate their ability to predict stream flow in the river under study with reasonable accuracy.